Islamic Education Research Problem - Abdul Muthalib (Intelektual Pustaka Media Utama, 2012)
This paper will discuss Islamic educational studies that is reviewing how to find, limit and define problems and problem-solving concepts. The central question of this paper is to describe how to solve the problem in Islamic educational research. A researcher or educator who has the knowledge, expertise, or special interest on education for example is usually having a sensitivity to issues relating to educational research. In the research dimension of religious education, there are three types of problems, namely: Problems foundation, structural problems and operational issues. In doing research in Islamic education someone should understand research problem, limiting and formulating the problem, how to solve the problem, other problem relating to the point of research, and research approach.